(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
Skinner’s thesis, that all words used to describe feelings started out as metaphors, was considered to be a "functional theory of metaphor". The aim of this paper is to describe the etymology of the names of feelings in Portuguese by means of an etymological-functional analysis in which the possible, original contingencies that might have controlled the emergence of these names were abstracted. The data comprised the names of five feelings analyzed through a combination of etymological and functional analysis. The results corroborate the Skinnerian thesis and they conclude with the original contingency that gave the radical meaning to the roots of words. The results point to the possibility of a functional analysis of additional elements of grammar that form the morphology of the words.